Ali Shahab: pelopor sinema elektronik di media televisi Indonesia tahun 1984-2004 - Patoni, Intan Ranti Permatasari; Martha, Nur'aeni; Humaidi, Humaidi (Historiography: Journal of Indonesian History and Education, 2024)
Abstract This research aims to explain the role of Ali Shahab as a pioneer of cinema in Indonesian television media for developing television cinema in the period of 1984 to 2004. This research uses historical methods with the descriptive narrative form as using primary sources from Ali Shahab's life history which was wrote by himself for the Indonesian Film Association’s data in 1997, and also using the secondary sources. The results of the research are Ali Shahab pioneered electronic cinema on Indonesian television media with the series "Rumah Masa Depan". And then, using the lastest technologies in the Indonesian cinema production process, and also built a natural studio called Studio Focus. There is great hope that this research can give the explanation of the role that Ali Shahab played as a pioneer of electronic cinema in Indonesian television media.Abstrak Penelitian ini memiliki tujuan untuk menjelaskan peran Ali Shahab sebagai pelopor sinema elektronik di media televisi Indonesia dalam mengembangkan sinetron pada tahun 1984 sampai 2004.  Penelitian ini menggunakan metode historis dalam bentuk deskriptif naratif dengan menggunakan sumber-sumber primer dari riwayat hidup Ali Shahab yang ditulis oleh dirinya sendiri untuk data Persatuan Artis Film Indonesia tahun 1997, serta sumber sekunder. Hasil penelitian yang ditemukan adalah Ali Shahab memelopori sinema elektronik di Indonesia dengan sinetron “Rumah Masa Depan”, kemudian menggunakan teknologi-teknologi terbaru dalam proses produksi sinema elektronik tersebut, dan membangun studio alam bernama Studio Focus. Besar harapan melalui penelitian ini dapat menggambarkan mengenai peran Ali Shahab sebagai pelopor sinema elektronik di media televisi Indonesia.